Human-Centred Design of Products And Services for the Circular Economy – A Review. (4th July 2018) - Lofthouse, Vicky; Prendeville, Sharon
Abstract: This paper aims to broaden the circular economy discussion by emphasizing the role of people. The paper combines core circular economy literature and user-centred design seed literature with illustrative case studies, to consider the positioning of design within a circular economy. The article observes that design is considered predominantly in positivist terms within a field dominated by management, engineering, ecological and environmental science literature. Conceptualizing the designer's opportunity within the circular economy would benefit from integration of knowledge from the social sciences (sociology of consumption, consumer psychology, cultural studies, inter alia ). The current orientation overlooks design as a 'radical humanist' paradigm and this has implications for how people are considered (from 'users-as-subjects' to 'people-as-participants') raising ethical questions about design practice within divergent circular economy framings. The article lays a basis for further research and theory-building for a fuller conceptualization of the designer's opportunity within the circular economy.